Role of Ab Initio Calculations in the Design and Development of Organometallic Lanthanide‐Based Single‐Molecule Magnets. Issue 23 (24th October 2019) - Swain, Abinash; Sarkar, Arup; Rajaraman, Gopalan
Abstract: Single‐molecule magnets based on lanthanides are very attractive due to their potential applications proposed in the area of microelectronic devices. Very recent advances in this area are due to the blend of conventional lanthanide chemistry with organometallic ligands, and several breakthrough achievements are attained with this combination. Ab initio methods based on multi‐reference CASSCF calculations are playing a vital role in the design and development of such molecules. In this minireview, we aim to appraise various contributions in the area of organometallic lanthanide complexes (those containing lanthanide‐carbon bonds) and describe how these robust wavefunction‐based methods have played a constructive role not only in rationalizing the observed magnetic properties but also proven to be a potential predictive tool with some selected examples. Abstract : The Ln−C magic wand : In this review, we have summarized various organometallic lanthanide complexes where ab initio calculations were utilized to understand the mechanism of magnetic relaxation and highlight the importance of Ln−C bonds in future devices.